2016
DOI: 10.3389/fnint.2016.00027
|View full text |Cite
|
Sign up to set email alerts
|

The Pointing Errors in Optic Ataxia Reveal the Role of “Peripheral Magnification” of the PPC

Abstract: Interaction with visual objects in the environment requires an accurate correspondence between visual space and its internal representation within the brain. Many clinical conditions involve some impairment in visuo-motor control and the errors created by the lesion of a specific brain region are neither random nor uninformative. Modern approaches to studying the neuropsychology of action require powerful data-driven analyses and error modeling in order to understand the function of the lesioned areas. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Additionally, greater severity of optic ataxia (Perenin & Vighetto, 1988) was observed in patients with left hemisphere injures. In particular, most patients with optic ataxia after a left hemisphere lesion have displayed a hand effect (errors when pointing with their contralesional hand) as well as a contralateral field effect (errors when pointing to stimuli in the contralesional visual hemifield) (Vindras et al, 2016), whereas patients with a right hemisphere lesion showed a milder version of optic ataxia with only a field effect (Perenin & Vighetto, 1988). TC’s deficit is consistent with the non-dichotomous specialization of the left hemisphere in visuomotor computations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, greater severity of optic ataxia (Perenin & Vighetto, 1988) was observed in patients with left hemisphere injures. In particular, most patients with optic ataxia after a left hemisphere lesion have displayed a hand effect (errors when pointing with their contralesional hand) as well as a contralateral field effect (errors when pointing to stimuli in the contralesional visual hemifield) (Vindras et al, 2016), whereas patients with a right hemisphere lesion showed a milder version of optic ataxia with only a field effect (Perenin & Vighetto, 1988). TC’s deficit is consistent with the non-dichotomous specialization of the left hemisphere in visuomotor computations.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of changing the perception angle by 20 • and 40 • to the right on the dart throwing results can manifest itself in a similar way with dysfunction of somato-spatial synthesis while correlating the object's location with the respect to one's body and constructing a corresponding action program. For example, a mismatch of visual and proprioceptive information is observed in patients with optic ataxia associated with a dysfunction of the parieto-occipital junction [47]. Conducting cognitive diagnostics in VR or cognitive rehabilitation in VR by using Vicariation or by restructuring functional systems, without taking into account the factor of perception distortion of the perspective and body proportions, can produce an inadequate assessment on the degree of cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Attentional disorders, for example, clinical spatial neglect, have been associated with lesions in the right TPJ (VAN) [11,12] but not with exclusive lesions in the IPS/SPL (DAN). Instead, clinical examination of patients with IPS/SPL lesions often reveals optic ataxia, a neurological deficit in which patients have no primary perceptual or motor deficits but present difficulties in responding to objects in the contralesional peripheral visual field [13][14][15][16][17][18][19][20], and in fast visuomotor transformations known to depend on interactions between the occipito-parietal region and the dorsal premotor and primary motor cortices (e.g., [21][22][23][24][25][26][27][28][29][30]). Interestingly, close examination of patients with focal IPS/SPL lesions and without clinical neglect syndrome, for example, by using briefly flashed stimuli, sometimes reveals attentional difficulties in the form of sub-clinical visual detection and discrimination deficits that are specific to covert endogenous orienting in the contralesional peripheral visual field [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%